Implementation of Problem Based Learning Model to Improve Learning Outcomes at SD Negeri Lawe Bulan - Suriani, Irma Fitri (MANDAILING GLOBAL EDUKASIA, 2025)
This classroom action research aims to improve the learning outcomes of fourth-grade students at SD Negeri Lawe Bulan in the topic of